Management of Evolving Contraints in a Computerised Engineering Design Environment - Goonethillake, J.S.; Wikramanayake, G.N. (My University, 2004)
Engineering design process has an evolutionary and iterative nature as design artifacts develop through series of changes before the final solution is achieved. Design is performed based on design requirements which are mainly specified as restrictions on the properties of the design artifact, and are considered to be design constraints. A common problem encountered during the design process is that of constraint evolution, which may involve the identification of new constraints and modification or omission of existing constraints for a number of reasons. These reasons would include changes in customer requirements, changes in the technology, change in the production cost or to improve the performance. As design is an evolutionary process where a solution is sought by trial and error, integrity constraints in engineering design will not remain fixed but will tend to evolve during the design process. This evolving nature of constraints has made the support for automatic integrity validation, non-trivial as it imposes number of key issues that need to be dealt with. We have been able to successfully address these issues with respect to the engineering design environment and we identify how one could meet the challenges through effective management of these evolving constraints for engineering designs. Thus the original design will continue to exist while supporting the creation of new design versions to meet the changes.
Keywords: computerised Engineering Design Environment